The defining of the reference range of liver stiffness and fat attenuation parameter for healthy Chinese children. Issue 11 (November 2021) - Zeng, Fansen; Wang, Haiyan; Li, Xufang
Abstract : Aims: We aimed to establish the basal reference levels of liver stiffness and accumulated fat in healthy Chinese children. Methods: To obtain the liver stiffness measurement (LSM) and the fat attenuation parameter (FAP) levels, the transient elastography (FibroTouch) was used in pediatric patients aged 0 to 18 years. The patients were divided into groups as follows: newborns/infants (0–2 years), preschool children (3–5 years), elementary school children (6–11 years), and adolescents/teenagers (12–18 years). The weight, height and fasting liver function tests were performed. FibroTouch and abdominal ultrasonography were performed. Results: The livers of 521 out of 1362 children (329 male; median age, 4.6 years; age range 0.2–17.6 years) were examined with the FibroTouch. The LSM reference range was 1.5–5.9 kPa, and the FAP reference range was 159.6–217.1 dB/m in healthy children from 0 to 18 years of age. The median LSM value was higher in males than that in females (3.5 vs. 3.2 kPa, respectively; P = 0.01). Conclusion: For healthy children from 0 to 18 years in southern China, the LSM reference range was 1.5–5.9 kPa, and the FAP reference range was 159.6–217.1 dB/m. The LSM values were age-dependent in children from 3 to 18 years old, and the FAP values were age-independent in children from 0 to18 years old.